Beneficial Role of Increased Glucose Infusion in Decompensated Type 2 Diabetes Patient - Marie Ticha; Ondrej Sobotka; Pavel Skorepa; Lubos Sobotka (Diabetology)
Introduction: Managing glycemic fluctuations in critically ill elderly patients with type 2 diabetes mellitus (T2DM) poses significant challenges. This case report presents a unique scenario in which increased intravenous glucose (Glc) infusion, together with insulin therapy, improved glycemic control and reduced insulin requirements during a septic episode. This finding adds to the scientific literature by suggesting that adequate Glc administration may enhance insulin sensitivity in critically ill T2DM patients. Case report: An 84-year-old female patient with T2DM, hypertension, and chronic renal failure was admitted to the intensive care unit with fever, nausea, loss of appetite, and profound weakness. Laboratory findings revealed severe hyperglycemia, electrolyte imbalances, and markedly elevated inflammatory markers, leading to the diagnosis of decompensated T2DM that was complicated by sepsis. The initial treatment consisted of continuous intravenous (IV) insulin, crystalloid infusions, and broad-spectrum antibiotics. Despite insulin therapy and the absence of nutritional intake, the patient experienced extreme fluctuations in their blood glucose levels, ranging from hyperglycemia to hypoglycemia. Due to persistent glycemic instability, IV Glc infusion was initiated alongside continuous insulin therapy. Paradoxically, increasing Glc infusion administration rate led to a reduction in the required insulin doses and stabilization of blood glucose levels below 10 mmol·L−1. The patient’s C-peptide levels were initially elevated but subsequently decreased following Glc administration as well, suggesting a reduction in endogenous insulin secretion and therefore higher insulin sensitivity. The patient’s clinical condition improved, allowing for the transition to a subcutaneous insulin regime and the initiation of oral feeding. She was later transferred to a general medical ward and discharged without further complications. Conclusions: This case highlights the complex interplay between Glc and insulin in critically ill elderly patients with T2DM during sepsis. The main takeaway is that carefully managed Glc infusion, in conjunction with flexible insulin therapy, can enhance insulin sensitivity and stabilize blood glucose levels without causing further hyperglycemia. Frequent glycemia monitoring and adaptable glycemic management strategies are essential in the ICU to address rapid glycemic fluctuations in this patient population.